Effects of Foot Orthoses and Kinesio Tape on Spatiotemporal and Kinetic Gait Parameters during Running in Individuals with Flatfoot - Chen, Hairong; Bíró, István (Analecta Technica Szegedinensia, 2024)
Flatfoot is a common condition that influences gait and can cause discomfort for patients under higher loaded condition, such as running. Identifying the most effective treatment necessitates a comprehensive analysis of each therapy’s impact on gait. Our research delved into the effects of Foot Orthosis and Kinesio Tape on the spatiotemporal and kinetic aspects of gait in individuals with flatfoot during running. Twenty female rearfoot strike runners with flatfoot participated in the running tasks at 3.3±5% m/s on the Zebris Medical GmbH treadmill. Gait data were collected under three conditions: shoe (A), shoe with Foot Orthoses (B), and shoe with Kinesio Tape (C). A one-way repeated measures ANOVA was employed to analyzed the gait parameters during the stance phase. Under conditions B and C, the foot rotation angle significantly decreased compared to condition A. Additionally, in condition B, it was significantly lower than in condition C. Under conditions B and C, the maximum force and pressure of forefoot significantly increased, whereas it in the midfoot significantly decreased, relative to condition A. Foot Orthosis and Kinesio Tape both effectively diminished peak midfoot pressure during running. Additionally, Foot Orthosis surpassed Kinesio Tape in enhancing foot stability and function throughout the running. These findings offered valuable insights for the selection of intervention measures for patients with flat feet during running.